Novel short antimicrobial peptide isolated from Xenopus laevis skin. (16th March 2017) - Zhang, Yu; Liu, Songcai; Li, Siming; Cheng, Yunyun; Nie, Linyan; Wang, Gang; Lv, Chen; Wei, Wenzhen; Cheng, Cheng; Hou, Feng; Hao, Linlin
Abstract : A rich source of bioactive peptides, including a large number of antimicrobial peptides, has been found in amphibian skin. In this study, a novel short antimicrobial peptide was purified from Xenopus laevis skin and characterised through reversed‐phase high‐performance liquid chromatography, Edman degradation and matrix‐assisted laser desorption/ionisation time‐of‐flight mass spectrometry. The peptide was composed of six amino acids with a sequence of DEDLDE and thus named X. laevis antibacterial peptide‐P2 (XLAsp‐P2). Transmission electron microscopy revealed that this peptide showed potential antimicrobial abilities against bacteria by damaging the bacterial cell membrane. XLAsp‐P2 maybe inhibit bacterial growth by binding to the microbial genomic DNA. The peptide also exhibited a weak haemolytic activity against rabbit red blood cells. Therefore, XLAsp‐P2 is a novel short anionic antibacterial peptide with broad activities. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Fractionations and purification of Xenopus laevis skin secretions. The peptide of peak no. 11‐7 was identified as a novel AMP, and named XLAsp‐P2.